2017
DOI: 10.1111/ina.12365
|View full text |Cite
|
Sign up to set email alerts
|

Emission rates and the personal cloud effect associated with particle release from the perihuman environment

Abstract: Inhalation exposure to elevated particulate matter levels is correlated with deleterious health and well-being outcomes. Despite growing evidence that identifies humans as sources of coarse airborne particles, the extent to which personal exposures are influenced by particle releases near occupants is unknown. In a controlled chamber, we monitored airborne total particle levels with high temporal and particle-size resolution for a range of simulated occupant activities. We also sampled directly from the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 46 publications
9
109
0
Order By: Relevance
“…19 There may also be significant contributions caused by direct shedding from the human envelope, including the release of previously deposited particles from clothing surfaces, hair, or bare skin. 20 Among the best PM exposure studies was the PTEAM investigation, which showed a substantial personal cloud effect for PM 10 . 21 A recent study documents that a contribution to the personal cloud can result when coarse particles are released into the perihuman space of a seated occupant with subsequent upward transport into the breathing zone by the action of the metabolically generated thermal plume.…”
Section: The Particles Around Usmentioning
confidence: 99%
See 3 more Smart Citations
“…19 There may also be significant contributions caused by direct shedding from the human envelope, including the release of previously deposited particles from clothing surfaces, hair, or bare skin. 20 Among the best PM exposure studies was the PTEAM investigation, which showed a substantial personal cloud effect for PM 10 . 21 A recent study documents that a contribution to the personal cloud can result when coarse particles are released into the perihuman space of a seated occupant with subsequent upward transport into the breathing zone by the action of the metabolically generated thermal plume.…”
Section: The Particles Around Usmentioning
confidence: 99%
“…21 A recent study documents that a contribution to the personal cloud can result when coarse particles are released into the perihuman space of a seated occupant with subsequent upward transport into the breathing zone by the action of the metabolically generated thermal plume. 20 Exposure to ultrafine particles is likewise poorly characterized. In outdoor air, one dominant feature is the strong spatially varying concentrations near heavily trafficked roadways.…”
Section: The Particles Around Usmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Several previous studies [19][20][21][22] experimentally measured the particle emission rates from clothed occupants and from various human activities in homes and classrooms, such as folding blankets, making a bed, vacuuming, walking around, and sitting. [23][24][25][26][27] They found that the factors affecting particle emission rates included the number of persons performing the activity, 22 the type and intensity of the activity, 24 the type of floor and seat cover, 23 the clothing level, 19 and the operational state of the mechanical ventilation system. 27 However, these factors would be very different in an airliner cabin environment from in an indoor environment in a building.…”
mentioning
confidence: 99%